Retrospective database analysis on the demographics and resource utilization of patients with Parkinson’s disease in Quebec, Canada - Véronique Baribeau; Shawn Mohammed; Amnah Awan; Diana Parison; Jean Lachaine (Clinical Parkinsonism & Related Disorders)
Introduction: Parkinson’s disease (PD) is the most prevalent neurodegenerative movement disorder. Despite its recognized significance, there remains a paucity of recent studies reporting treatment utilization and the economic impact of PD in a real-world setting, especially in Canada. This study aimed to analyze real-world treatment patterns and health care resource utilization (HCRU) of patients with PD in Quebec, Canada. Methods: This was a retrospective observational study using data between 2010–2019 from the Régie de l’assurance maladie du Québec (RAMQ) databases. Patients with PD were compared to age- and sex-matched controls. Treatment adherence and persistence were measured over 24 months. All-cause and PD-related HCRU and costs were characterized on an annual basis. Results: Overall, 303 PD patients and 909 age- and sex-matched controls were selected. Adherence rates were high (≥85 %) among all drug classes, but lower with dopamine agonists. Persistence to PD treatment declined over time, with nearly 50 % discontinuation rates at 24 months in all PD drug classes, except the levodopa class (discontinuation rate: 20.4 %). PD patients had a significantly higher total costs per year than the matched control group ($17,405 vs. $6,431), mainly driven by higher inpatient costs. Conclusion: Many pharmacological options exist for PD patients and, though patients are adherent while on therapy, treatment discontinuation rates are high. This suggests potential long-term challenges in PD management, especially since PD continues to place a substantial burden on the health care system. This study underscores the need for enhanced therapeutic strategies, particularly for patients inadequately controlled with standard therapies.